The role of insufficient copper in lipid synthesis and fatty‐liver disease. Issue 4 (8th March 2017) - Morrell, Austin; Tallino, Savannah; Yu, Lei; Burkhead, Jason L.
Abstract: The essential transition metal copper is important in lipid metabolism, redox balance, iron mobilization, and many other critical processes in eukaryotic organisms. Genetic diseases where copper homeostasis is disrupted, including Menkes disease and Wilson disease, indicate the importance of copper balance to human health. The severe consequences of insufficient copper supply are illustrated by Menkes disease, caused by mutation in the X‐linked ATP7A gene encoding a protein that transports copper from intestinal epithelia into the bloodstream and across the blood–brain barrier. Inadequate copper supply to the body due to poor diet quality or malabsorption can disrupt several molecular level pathways and processes. Though much of the copper distribution machinery has been described and consequences of disrupted copper handling have been characterized in human disease as well as animal models, physiological consequences of sub‐optimal copper due to poor nutrition or malabsorption have not been extensively studied. Recent work indicates that insufficient copper may be important in a number of common diseases including obesity, ischemic heart disease, and metabolic syndrome. Specifically, marginal copper deficiency (CuD) has been reported as a potential etiologic factor in diseases characterized by disrupted lipid metabolism such as non‐alcoholic fatty‐liver disease (NAFLD). In this review, we discuss the available data suggesting that a significant portion of the North American population may consume insufficient copper, the potential mechanisms by which CuD may promote lipid biosynthesis, and the interaction between CuD and dietary fructose in the etiology of NAFLD. © 2016 IUBMB Life, 69(4):263–270, 2017